Aligning patient and physician views on educational pelvic examinations under anaesthesia: the medical student perspective. Issue 6 (21st September 2020) - Salwi, Sanjana; Erath, Alexandra; Patel, Pious D; Kaur, Karampreet; Mitchell, Margaret B
Abstract : Recent media articles have stirred controversy over anecdotal reports of medical students practising educational pelvic examinations on women under anaesthesia without explicit consent. The understandable public outrage that followed merits a substantive response from the medical community. As medical students, we offer a unique perspective on consent for trainee involvement informed by the transitional stage we occupy between patient and physician. We start by contextualising the role of educational pelvic examinations under anaesthesia (EUAs) within general clinical skill development in medical education. Then we analyse two main barriers to achieving explicit consent for educational pelvic EUAs: ambiguity within professional guidelines on how to operationalize 'explicit consent' and divergent patient and physician perspectives on harm which prevent physicians from understanding what a reasonable patient would want to know before a procedure. To overcome these barriers, we advocate for more research on patient perspectives to empower the reasonable patient standard. Next, we call for minimum disclosure standards informed by this research and created in conjunction with students, physicians and patients to improve the informed consent process and relieve medical student moral injury caused by performing 'unconsented' educational pelvic exams.